Factor V Leiden and Thrombotic Complications in Heparin-induced Thrombocytopenia - Lee, David H.; Warkentin, Theodore E.; Denomme, Gregory A.; Lagrotteria, Danny D.; Kelton, John G. (Thrombosis and Haemostasis, 1998)
To determine whether factor V Leiden is associated with thrombotic events in patients with heparin-induced thrombocytopenia (HIT), we evaluated 165 patients with serologically confirmed HIT for the presence of factor V Leiden and determined the incidence of venous or arterial thrombosis during the period of HIT. Factor V Leiden was detected in 16 of 165 HIT patients (9.7%). HIT-associated venous thrombosis occurred in 11 of 16 factor V Leiden positive subjects and 94 of 149 factor V Leiden negative subjects (69% vs. 63%; p = 0.79). Arterial thrombosis occurred in 1 of 16 factor V Leiden positive subjects and 21 of 149 factor V Leiden negative subjects (6% vs. 14%; p = 0.70). There was no difference in the incidence of proximal limb DVT, pulmonary embolism, venous limb gangrene, local skin reactions, hemorrhagic adrenal infarction, stroke, or myocardial infarction between the groups. No difference in the severity of venous thrombosis between Leiden positive and negative subjects was detected. Our data suggest that in the acute prothrombotic milieu of HIT, heterozygous factor V Leiden is not an important additional risk factor for thrombosis.